Manhaj Tafsir Al-Mizan Fi Tafsir al-Quran karya Muhammad Husain Thabathaba’i - Fatimah Isyti Karimah; Iwan Caca Gunawan (Jurnal Iman dan Spiritualitas, 2022)
The affirmative era is a continuation of the formative era. This era occurred in the Middle Ages, when the tradition of interpreting the Qur'an already had many specific and varied features. This era is also judged to be based on ideological reasoning. Tafsir al-Mizan is included in the category of interpretation in the affirmative era because some of its interpretations are based on the ideological rationale of the exegete, namely Muhammad Husain Tabataba'i. This study aims to describe the manhaj used in Tafsir Al-Mizan Fi Tafsir al-Quran by Muhammad Husain Tabataba'i in studying a verse of the Koran. The methods used in this research are the library research method and descriptive analysis. The results from this research are: Tafsir al-Mizan is a phenomenal work by Muhammad Husain Tabataba'i. His work is inseparable from the author's thoughts, who has a philosophical background in thinking. Even so, the interpretation uses the uslub of the Qur'an, bil Qur'an, and also contains many other commentators' opinions. So the interpretation is called a "very complete interpretation" because it contains many fields of knowledge. The special manhaj or method of writing the interpretation of al-Mizan, namely interpreting the book in sequential order, explains the purpose of the interpreted surah or verse, cites the opinions of the reviewers of the Qur'an and also presents his view, has its section on the discussion of history, specializes in the discussion of philosophical aspects, and provides general conclusions from the verse or letter being studied.